Encephalitis - Tkachev, Sergey (IntechOpen, 2013)
Encephalitises are a group of inflammatory human and animal diseases of brain caused essentially by different pathogens. In spite of evident success in approaches for prevention, diagnostics and treatment during the last decades, the encephalitises of different etiology still constitute a menace for thousands of people all around the world. In this book the different aspects of encephalitises of different etiology are discussed such as diagnostics, treatment and clinical management of patients. Also, the data on epidemiology, monitoring, pathology and diagnostics of different viral causative agents are discussed.